Talking but not always understanding: couple communication about infertility concerns after cancer - Alexandra Hawkey; Jane M. Ussher; Janette Perz; Chloe Parton (BMC, 2021)
Abstract Background Cancer related infertility can have an impact on couple relationships, with evidence that couple communication facilitates coping. However, little is known about the ways in which couples communicate about cancer-related fertility concerns. The aim of this article is to examine couple communication about fertility concerns in the context of cancer, and the perceived quality of such communication from the perspective of cancer survivors and their partners. Methods Eight-hundred and seventy-eight cancer survivors (693 women, 185 men) and 144 partners (82 women, 62 men), across a range of tumour types and age groups, completed a survey which examined cancer related fertility concerns. Seventy-eight survivors (61 women and 17 men), and 26 partners (13 women and 13 men), participated in semi-structured interviews, in order to examine the subjective experience of fertility concerns in-depth. Thematic analysis was used to analyse the interviews and open ended survey questions. Valid percentages for single items from the relationships subscale of the Fertility Preservation Inventory (FPI) related to qualitative themes, identified frequency of responses. Results The major theme was 'talking but not always understanding". 89.6% of cancer survivors and partners (95.1%) reported working well together handling fertility questions (FPI), but agreed that communication could be improved (65.9% survivors; 65% partners). Open and honest couple communication was associated with feelings of support, understanding and relationship growth, including perception of partner comfort (79.2% survivors, 81.6% partners). However, 32% survivors and 31.1% partners concealed fertility concerns to avoid upsetting their partner, or reported that their partner doesn't understand their fertility concerns (survivors 25.5%, partners 14.6%), with 14.1% of cancer survivors and 19.4% partners reporting fear of relationship breakdown because of fertility issues. Fear of rejection when forming new relationships, and concerns about how to talk to future partners, was reported by non-partnered individuals. Conclusion Health-care professionals should include partners of cancer survivors in fertility discussions. Couple interventions developed in general psycho-oncology should be extended to the domain of fertility, in order to facilitate effective couple communication. Communication in future relationships needs to be addressed for single people and adolescents and young adults (AYAs) who have fertility concerns.